Adaptation of elderly people and various inequalities in the post-pandemic time - K. A. Galkin (Вестник университета)
The article studies situational inequalities emerged during the pandemic and peculiarities of adaptation of elderly people in the post-pandemic time. The research focuses on everyday projections of inequalities of elderly people living separately in the federal city and rural areas. To examine inequalities, the paper uses microsociological optics. It made it possible to analyze how structural inequalities affect the lives of the elderly and what are the ways to adapt after the pandemic that triggered the processes of protection and self-preservation. The empirical base of the study is 30 semi-structured interviews collected in 2022 in St. Petersburg and villages of the Republic of Karelia. The article describes such situational inequalities as digital inequalities, inequalities in accessing and receiving information, spatial inequalities, and inequalities in receiving medical care as main inequalities. The study concludes that emotional reflection, availabilities of hobbies or emergence of new ones, revision of previous resources, types of communication and ways of solving problems, shift of focus from caring for family and relatives to caring for themselves create positive opportunities for adaptation for older people.